A educação do campo e os desafios de professores em classes multisseriadas nas escolas do município de Inhangapi-Pará -2018 - SOUZA, Regiane Menezes de (2020)
The present study presents as a theme the teaching challenges in multisite classes of rural schools in the municipality of Inhangapi-Pará, whose main objective is to analyze the challenges faced by teachers who teach in multi-grade classes in rural schools in the municipality of Inhangapi-PA. We used as a data collection technique the semi-structured interview with three teachers from the Municipal School of Early Childhood Education and Elementary School of Maracanã, Municipal School of Early Childhood Education and Cumaru Elementary School and Municipal School of Early Childhood Education and Elementary School of Alto Patauateua, all located in the field and operate on multi-series classes. As a theoretical contribution, we chose authors, such as Arroyo (1999); Arroyo, Caldart and Molina (2004), Brandão (2001); Caldart (2002, 2004, 2012); Hage (2005, 2011); Kolling, Nery and Molina (1999); in addition to education legislation, such as LDB 9394/96, and the Operational Guidelines for Basic Education in Field Schools (2002, 2008), among others. Based on the data collected and analyzed, we infer that there is still more investment in education that is offered in the rural schools, and that the challenges are great for a single teacher to teach in a single classroom with several grades and ages in one environment.